Inobservancia en la fijación de las pensiones máximas de arrendamiento por parte de las oficinas de registro de arrendamientos o jefaturas de catastros municipales. - Bustán Ordóñez, Richard Heraldo (2013)
The present Thesis contains a study of the Ecuadorian reality artificial partner, as soon as he/she refers to the Code of the Law of Tenancy in its Article 10 essentially, the same one that textually says: "Fixation of the maximum pensions of lease. - The Offices of Registration of Leases or the Headquarters of Municipal Cadasters, according to the case, will fix the maximum pension of lease of each local, and they will give to the lessor, in the maximum term of four months, a certificate in which consists the identity of the property or inscribed local and the monthly pension for their lease." In the context of this investigative work, I consider of urgent necessity to reform the Law of Tenancy, since the Municipal Entity, through their Offices in charge of the fixation of the maximum pension of lease of each local, they have in observation permanently this legal disposition, without considering that ordered by the Constitution of the Republic of the Ecuador. I also consider in the conclusions of this final report of thesis that in front of the constant neglect of the Constitutional norm and the Law of Tenancy, the Offices of Registration of Leases, they should pass to form part of the Tribunals of Tenancy and being these who fix the maximum pension of leases and to take the control.